The Pegasus workflow management system: Translational computer science in practice - Deelman, Ewa; Ferreira da Silva, Rafael; Vahi, Karan; Rynge, Mats; Mayani, Rajiv; Tanaka, Ryan; Whitcup, Wendy; Livny, Miron (Journal of computational science, 2021)
•Analysis of translational computer science with the lens of the Pegasus experience.•Application of TCS principles into the research and development process of Pegasus.•Discussion of challenges and potential solutions regarding translational research. Translational research (TR) has been extensively used in the health science domain, where results from laboratory research are translated to human studies and where evidence-based practices are adopted in real-world settings to reach broad communities. In computer science, much research stops at the result publication and dissemination stage without moving to the evaluation in real settings at scale and feeding the gained knowledge back to research. Additionally, there is a lack of steady funding and incentives to broadly promote translational computer science (TCS) in practice. In this paper, we present how, throughout its lifespan, the Pegasus workflow management system project has incorporated the principles of translational computer science. We report on our experience on building a strong, long-term engagement with a broad range of science communities to establish mutually beneficial relationships between the core R&D team and these communities.